The Influence of Shoot Location and Mechanical Treatment Following Grafting on Siamese Orange Seedling Development - Fitri Yetty Zairani; Burlian Hasani (Journal of Global Sustainable Agriculture, 2022)
This study aims to determine the influence of the location of the buds and mechanical treatment after grafting on the growth of orange seedlings. The study used a Randomized Group Design (RAK), arranged factorially with nine combinations of treatments and three tests. The first treatment factor used is the budding eye system (P), consisting of 3 levels, namely P1: Fourth Budding Eye; P2: Fifth Budding Eye; and P3: Sixth Budding Eye.   The second factor is mechanical treatment after grafting (K) consisting of 3 levels, namely K1: Rootstock Cutting; K2: Rootstock Restraint; and K3: Rootstock Bending. The parameters observed are the percentage of grafting of living plants, the time of bud exit, the number of leaf blades, the twisting of the stem of the grafting bud, and the length of the grafting bud. Based on the observations on the percentage of grafting that live after mechanical treatment of all budding eye location treatments, it shows that the fifth bud (P2) location treatment gives a higher rate of live grafting, which is 100% compared to other treatments. The treatment of the location of the fifth bud gives the best results against the time of bud exit, the number of leaves, the twisting of the grafting stem and the length of the grafting bud. Mechanical treatment of rootstock restraint after grafting gives the best results against the time of bud exit, the number of leaves, the twisting of the grafting stem and the length of the grafting bud. The interaction between the treatment of the fifth bud location treatment and the mechanical treatment of rootstock holding gave the best results against the growth of Siamese orange seedlings.